Analisis Pengaruh Implementasi Teknologi Informasi Terhadap Kinerja Karyawan - Siska Narulita; Suhaji Suhaji; Retno Ginanjar (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2022)
The purpose of this study was to analyze the effect of perceived ease of use and perceived usefulness of information technology on employee performance of telecommunication companies in the city of Semarang. The number of population in this study was 75 employees and the number of samples was 63 employees. The sampling technique used probability with simple random sampling. The analysis technique used was multiple linier regression. Based on the hypothesis testing partially, the result showed that perceived ease of use of information technology had a significant positive effect and perceived usefulness of information technology didn’t have an effect on employee performance of telecommunication companies in the city of Semarang.